Effect of Nano–Palm Kernel Shell Biochar on Cure, Swelling, and Mechanical Properties of Natural Rubber Vulcanizates - Mohammad Tahar Nur Aisyah Ar-Raudhoh; Mohd Fadzli Muhamad Haziq; Mamauod Siti Nur Liyana; Zainal Nahrul Hayawin (BioResources)
The rapid growth in Malaysia’s oil palm industry has resulted in the increase in production of palm oil and oil palm waste such as palm kernel shell (PKS). However, the lack of awareness on the beneficial value of these wastes has led to sustainability issues. Thus, PKS can be converted into biochar (PKSB) and can be used as a potential bio-filler. The PKSB was produced in sizes ranging from micro to nano using a high energy ball mill (HEBM) to be used as a filler in natural rubber (NR) vulcanizates. This study evaluated the effects of varying n-PKSB loadings (0 to 10 phr) on the cure characteristics, bound rubber content (BRC), swelling, tensile, and abrasion properties of the NR vulcanizates. Results showed that n-PKSB-filled NR vulcanizates had lower minimum torque (ML) and cure rate index (CRI), along with improved BRC and crosslink density as the filler concentrations increased. The optimum loading ratio was 5 phr (F4), as this formulation offered the best mechanical properties and more homogenous dispersion of n-PKSB compared to other loadings. The overall performance of F4 showed high crosslink density (7.82 x 10-5 mol/cm3), BRC (3.94%), tensile strength (17 MPa), abrasion resistance (32.37%), and lower EB (451%). Overall, n-PKSB has great potential as bio-filler, addressing oil palm waste issues and benefiting the industry.